The evaluation of bis(4-ethylphenylsulfonyldithiocarbimato)zincate (II) (ZNIBU) activity in the vulcanization of NBR compounds and its effect on their mechanical properties - de Oliveira, Iara; Cunha, Leandro; Visconte, Leila; Oliveira, Marcelo; Rubinger, Mayura (Publishing House of Lviv Polytechnic National University, 2010)
The effect of accelerator type on the vulcanization process and mechanical properties of nitrile rubber (NBR) compounds was investigated. Three commercial accelerators were selected, N-N-t-butyl-2- benzothiazole sulfenamide (TBBS), tetramethylthiuram disulfide (TMTD) and bis(dimethyldithiocarbamato)zinc (II) (ZDMC) and compared with the compound bis(4methylphenylsulfonyldithiocarbimato)zincate (II) (ZNIBU). Surprisingly, it was found that the optimum vulcanization time for ZNIBU showed better results than for TBBS. Вивчено вплив природи прискорювача вулканізації на перебіг процесу і механічні властивості нітрилових каучуків (НК). Проведено порівняння N, N-трет-бутил-2-бензотіазолсульфенаміду, дисульфіду тетраметилтиураму та біс(диметилдитіокарбамато)цинкату (ІІ) з біс(4-метилфенілсульфонілдітіокарбімато)цинкатом (ІІ). Встановлено, що оптимальний час вулканізації досягається на досліджуваному прискорювачі.
Оцінка активності біс(4-метилфенілсульфонілдитіокарбімато) цинкату (ІІ) в процесі вулканізації і його вплив на механічні властивості компонентів НК
Keywords: dithiocarbimates; zinc complexes; vulcanization; mechanical properties; nitrile rubber; дитіокарбімати; комплекс цинку; вулканізація; механічні властивості; нітриловий каучук